2020
DOI: 10.1186/s12866-020-01858-9
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent activity of silver nanoparticles on the morphological switch and biofilm formation of opportunistic pathogenic yeasts

Abstract: Background: Dimorphism and biofilm formation are important virulence factors of some opportunistic human pathogenic yeasts. Such species commensally colonize skin or mucosal surfaces generally in yeast form, but under particular circumstances, convert into virulent hyphae and disseminate internal organs or cause mucocutaneous infections. The yeast-to-hypha shape-conversion promotes the development of a biofilm, a thick extracellular matrix with sessile cells within. The biofilm is capable to prevent the penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
19
1
Order By: Relevance
“…Another rather valuable property of AgNPs is their biofilm-eradicating capability [ 218 , 219 ]. Biofilm formation is a very important virulence factor of several pathogenic bacteria and yeasts.…”
Section: Biological Activitymentioning
confidence: 99%
“…Another rather valuable property of AgNPs is their biofilm-eradicating capability [ 218 , 219 ]. Biofilm formation is a very important virulence factor of several pathogenic bacteria and yeasts.…”
Section: Biological Activitymentioning
confidence: 99%
“…All chemicals were purchased from Merck KGaA (Darmstadt, Germany). PVPstabilized silver nanoparticles (AgNP@PVP) were prepared by chemical reduction based on the approach proposed by Wan et al with slight adjustments, the same procedure that we used in our previous contributions [18,48,49]. While the original method is based on the chemical reduction of silver nitrate (AgNO 3 ) by sodium borohydride (NaBH 4 ) with sodium citrate capping, here we used PVP in two different (40k and 55k) average molecular weights as stabilizing agents.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…2 In agreement with the general literature, our previous studies have demonstrated the size-dependent activity of nanosilver on mammalian cells and microbes alike. [3][4][5] Surface coating is another attribute that has widespread effects on the properties of nanomaterials. The same nanomaterial might possess widely different physical, chemical, and biological characteristics just by adding, or modifying stabilizing agents on its surface.…”
Section: Introductionmentioning
confidence: 99%